Application of EU tissue and cell directive screening protocols to anonymous oocyte donors in western Ukraine: data from an Irish IVF programme. - Walsh, A; Omar, AB; Collins, G; Murray, G; Walsh, D; Salma, U; Sills, E (2010)
Anonymous oocyte donation in the EU proceeds only after rigorous screening designed to ensure gamete safety. If anonymous donor gametes originating from outside EU territory are used by EU patients, donor testing must conform to the same standards as if gamete procurement had occurred in the EU. In Ireland, IVF recipients can be matched to anonymous donors in the Ukraine (a non-EU country). This investigation describes the evolution of anonymous oocyte donor screening methods during this period and associated results. Data were reviewed for all participants in an anonymous donor oocyte IVF programme from 2006 to 2009, when testing consistent with contemporary EU screening requirements was performed on all Ukrainian oocyte donors. HIV and hepatitis tests were aggregated from 314 anonymous oocyte donors and 265 recipients. The results included 5,524 Ukrainian women who were interviewed and 314 of these entered the programme (5.7% accession rate). Mean age of anonymous oocyte donors was 27.9 years; all had achieved at least one delivery. No case of hepatitis or HIV was detected at initial screening or at oocyte procurement. This is the first study of HIV and hepatitis incidence specifically among Ukrainian oocyte donors. We find anonymous oocyte donors to be a low-risk group, despite a high background HIV rate. Following full disclosure of the donation process, most Ukrainian women wishing to volunteer as anonymous oocyte donors do not participate. Current EU screening requirements appear adequate to maintain patient safety in the context of anonymous donor oocyte IVF.